Overcoming chemoresistance in glioblastoma by fluvastatin via prenylation-dependent inhibition of Ras signaling. (2nd September 2022) - Long, Cheng; Yuan, Limei; Wei, Wei; Li, Jingwen
The resistance of glioblastoma to chemotherapy remains a significant clinical problem. Targeting alternative pathways such as protein prenylation is known to be effective against many cancers. Fluvastatin is a potent competitive inhibitor of 3-hydroxy-3-methylglutaryl- CoA (HMG-CoA) reductase, thereby inhibits prenylation. We demonstrate that fluvastatin alone effectively inhibits proliferation and induces apoptosis in multiple human glioblastoma cell lines. The combination index analysis shows that fluvastatin acts synergistically with common chemotherapy drugs for glioblastoma: temozolomide and irinotecan. We further show that fluvastatin acts on glioblastoma through inhibiting prenylation-dependent Ras activation. The combination of fluvastatin and low dose temozolomide resulted in remarkable inhibition of glioblastoma tumor in mice throughout the whole treatment duration without causing toxicity. Such combinatorial effects provide the basis for utilizing these FDA-approved drugs as a potential clinical approach in overcoming resistance and improving glioblastoma treatment.